2022
DOI: 10.3390/diagnostics12092120
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Rapid Low-Cost Procedure for Detection of Vancomycin-Resistance Genes in Enterococci Reveals an Outbreak of Vancomycin-Variable Enterococcus faecium

Abstract: The detection of resistance to vancomycin in enterococci cultured from patients is important for the treatment of individual patients and for the prevention of hospital transmission. Phenotypic antimicrobial resistance tests may fail to detect potential vancomycin-resistant enterococci. We have developed and tested a PCR based procedure for routine screening for vancomycin-resistance genes in clinical samples with enterococci. Primary cultures from diagnostic samples reported with growth of Enterococcus faeciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…More recently, vanA - or vanB -carrying enterococci [ 449 ] which appear vancomycin-susceptible in traditional phenotypic susceptibility tests [ 450 ], but can revert to a vancomycin-resistant phenotype upon vancomycin treatment [ 451 , 452 ] were reported for the first time in 2011 [ 453 ]. The ability of these strains, termed vancomycin-variable enterococci (VVE), to evade diagnostic tests and switch phenotypes during antibiotic therapy [ 452 ] is thought to be due to major deletions in the Tn 1546 vanA operon [ 453 ] and/or inducible or constitutive vanHAX expression [ 454 ] which significantly compromises treatment success [ 452 ].…”
Section: Vancomycinmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, vanA - or vanB -carrying enterococci [ 449 ] which appear vancomycin-susceptible in traditional phenotypic susceptibility tests [ 450 ], but can revert to a vancomycin-resistant phenotype upon vancomycin treatment [ 451 , 452 ] were reported for the first time in 2011 [ 453 ]. The ability of these strains, termed vancomycin-variable enterococci (VVE), to evade diagnostic tests and switch phenotypes during antibiotic therapy [ 452 ] is thought to be due to major deletions in the Tn 1546 vanA operon [ 453 ] and/or inducible or constitutive vanHAX expression [ 454 ] which significantly compromises treatment success [ 452 ].…”
Section: Vancomycinmentioning
confidence: 99%
“…Therefore, it is likely that current epidemiological estimates of VVE, particularly in developing countries, would be below its actual prevalence value. To combat this, molecular-based testing methods such as PCR are required [ 450 ], but the facilities and apparatus for these techniques may be limited in low- and middle-income regions.…”
Section: Vancomycinmentioning
confidence: 99%
“…As a major pathogen responsible for nosocomial infections, E. faecium isolates have often been found in surgical wound and urinary tract infections ( Huang et al., 2021 ; Strobel et al., 2022 ). Epidemiological investigations have found that VRE caused hospital outbreaks in various occasions ( Szakacs et al., 2014 ; Sivertsen et al., 2016 ; Hammerum et al., 2019 ; Abdullah et al., 2022 ), while E. faecium with dual resistance to linezolid and vancomycin was involved in the E. faecium outbreak in Reunion Island in 2019 ( Kamus et al., 2022 ). In terms of specific MDR, antibiotics such as cephalosporins, macrolides and semi-synthetic penicillin-like beta-lactams demonstrate prominent levels of resistance ( Guirao et al., 2009 ; Kristich et al., 2014 ; Georges et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%